The Role of Women Leaders in Character Development of Santri: (Leadership of Mrs. Nyai Umi Waheeda at the Al Ashriyyah Nurul Iman Parung Islamic Boarding School, Bogor) - Siti Maesaroh; Hasyim Asy'ari; Muhamad Syukur (PT ARRUS Intelektual Indonesia, 2024)
The aim of the research is to analyze the role, style and impact of Mrs. Nyai Ummi Waheeda's leadership in developing the character of students at the Al Ashriyyah Nurul Iman Parung Bogor Islamic boarding school. Based on these objectives, this research is qualitative research with a case study approach. The results of the research findings are: First, the leadership role of Mrs. Nyai Umi Waheeda in developing the character of the students is reflected in two aspects, namely task behavior and relationship behavior. In her duties, Umi prepares programs systematically, monitors the program periodically, and organizes the structured character of the students through Islamic boarding school rules and regulations. In the relationship aspect, Umi provides material and non-material support to students and administrators, communicates every policy before it is decided, and interacts easily. Second, the leadership style applied includes developing the character of students, namely the Telling, Selling, Participating and Delegating models. Umi with the telling model provides clear instructions. Each activity is controlled in 3 stages, the planning stage through the activity implementation plan (RPK), the implementation stage through the event report (BAP) and the evaluation stage through the activity accountability report (LPJK). The selling model is implemented by Umi through the support that is always given to the student character development program, instructions are delivered in communicative language. In the participating model, Umi always encourages students and administrators to take risks and develop. Meanwhile, Umi applies the Delegating model for various technical decisions to Islamic boarding school administrators. Each of these styles can be implemented well based on Fiedler's contingency theory because Umi Waheeda as a leader has a good relationship with the management, has a high task structure, and has a strong leadership position. Third, the impact of Mrs. Nyai's leadership can be seen from 3 aspects of moral knowledge, moral attitudes and moral behavior of students. The moral values taught and exemplified directly by Umi Waheeda include discipline, punctuality, maintaining cleanliness, sharing, caring for others, competitive, religious, highly committed and mutually respectful